2017
DOI: 10.1111/eos.12347
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of organic components in resin‐modified pulp capping materials: critical considerations

Abstract: The purpose of this study was to elucidate the organic composition and eluates of three resin-based pulp-capping materials in relation to their indications and safety data sheets. Uncured samples of Theracal LC, Ultra-Blend Plus, and Calcimol LC were investigated using gas chromatography-mass spectrometry (GC-MS) and ultra-performance liquid chromatography-mass spectrometry (UPLC-MS). Identification/quantification of 7-d leachables of cured samples was performed using GC-MS for 2-hydroxyethyl methacrylate (HEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 50 publications
4
34
0
6
Order By: Relevance
“…However, the high content of calcium silicate cement in Theracal LC can cause poor light transmission, and it also contains high molecular weight monomers, leading to a low level of polymerization (Alshali, Silikas, & Satterthwaite, ). A previous study observed that the polymerization of Theracal LC specimens with a 1‐mm thickness was not completed at the bottom surface, suggesting the Theracal LC contents are not optimal for light curing (Nilsen, Jensen, Ortengren, & Michelsen, ). The lower polymerization rate at the bottom surface leads to less polymerization stress and consequently, good adaptation, but this result in more released resin monomers, which could be detrimental for pulp cells in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…However, the high content of calcium silicate cement in Theracal LC can cause poor light transmission, and it also contains high molecular weight monomers, leading to a low level of polymerization (Alshali, Silikas, & Satterthwaite, ). A previous study observed that the polymerization of Theracal LC specimens with a 1‐mm thickness was not completed at the bottom surface, suggesting the Theracal LC contents are not optimal for light curing (Nilsen, Jensen, Ortengren, & Michelsen, ). The lower polymerization rate at the bottom surface leads to less polymerization stress and consequently, good adaptation, but this result in more released resin monomers, which could be detrimental for pulp cells in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Those findings were attributed to the presence of acrylic monomer Bis-GMA in the material. However, it should be noted that Bis-GMA was not detected, despite being listed in the safety data sheet provided by the supplier [124]. Presence of resin in the pulp capping agent which may remain unpolymerized is often associated with adverse pulpal reactions that lead to pulp toxicity and inflammation.…”
Section: Theracal Lcmentioning
confidence: 99%
“…However, despite having a similar CAS number, the substances in the reference substance did not match the substances present in ceram.x universal. A similar problem concerning reference substances and CAS numbers has been previously reported . A CAS registry number is a unique numeric identifier that designates only one substance .…”
Section: Discussionmentioning
confidence: 56%